Case report: Heart failure secondary to myocardial infarction in a fertile woman with woven coronary artery - Hu, Jiayi; Wang, Qian; Dong, Mei; Lu, Huixia (Frontiers in Cardiovascular Medicine, 2022)
A 42-year-old female was hospitalized with 2-day history of fever, dyspnea, and chest tightness. Four years ago, she had similar symptoms at the eighth week of gestation. Computed tomography coronary angiography only suggested moderate stenosis, but cardiac MRI indicated myocardial infarction. The coronary angiography demonstrated a woven coronary artery. She underwent successful coronary artery bypass grafting surgery and took medication regularly. Finally, the prognosis was favorable. Cardiovascular events seldom happen in fertile women because of the protection of estrogen, but once it occurs, the potential cause, such as coronary anomaly and other risk factors, should not be overlooked.